THE SALE AND PURCHASE OF FURNITURE WITH ISTISNA' CONTRACT ACCORDING TO ISLAMIC LAW: A Case Study in Sukakarya Sub-District, Sabang - Aris Munandar; Safira Mustaqilla (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2022)
The sale and purchase of furniture in Sukakarya Subdistrict, Sabang is generally carried out by means of an order (istiṣnā'). The problems in this study are how the practice of buying and selling furniture in Sukakarya Subdistrict, Sabang, and how Islamic Law views the delay in the delivery of goods in the istiṣnā' contract in buying and selling furniture in Sukakarya Subdistrict, Sabang. The results of this study show that order buying is permissible as long as all the conditions and pillars are fulfilled. The delay in delivery of goods in the sale and purchase of furniture in Sukakarya Subdistrict, Sabang is a violation of the sale and purchase agreement. The sale and purchase agreement is clear and agreed upon by both parties, but one of the parties, namely the seller, does not fulfil his obligations (does not deliver the goods at the specified time). According to Islamic law in this sale and purchase, the seller is obliged to deliver the goods even if he has to delay it temporarily. Delaying the delivery of goods is allowed if the person is in a difficult situation, then a time limit can be given according to the agreement.